Gut microbial diversity and stabilizing functions enhance the plateau adaptability of Tibetan wild ass (Equus kiang). Issue 6 (10th March 2020) - Gao, Hongmei; Chi, Xiangwen; Li, Guangying; Qin, Wen; Song, Pengfei; Jiang, Feng; Liu, Daoxin; Zhang, Jingjie; Zhou, Xiaowen; Li, Shengqing; Zhang, Tongzuo
Abstract: Interactions between gut microbiota not only regulate physical health, but also form a vital bridge between the environment and the host, thus helping the host to better adapt to the environment. The improvement of modern molecular sequencing techniques enables in‐depth investigations of the gut microbiota of vertebrate herbivores without harming them. By sequencing the 16S rRNA V4‐V5 region of the gut microbiota of both the captive and wild kiang in winter and summer, the diversity and function of the microbiota could be compared. The reasons for observed differences were discussed. The results showed that the dominant phyla of the kiang were Bacteroidetes and Firmicutes, and the structure and abundance of the gut microbiota differed significantly between seasons and environments. However, the relatively stable function of the gut microbiota supplies the host with increased adaptability to the environment. The diversity of the intestinal flora of the kiang is relatively low in captivity, which increases their risk to catch diseases to some extent. Therefore, importance should be attached to the impact of captivity on wildlife. Abstract : The alpha diversity of gut microbiomes in the wild group was significantly higher than that in the captive group. The content of pathogenic bacteria increased in the captive group. The health level of the captive kiang was lower than that of the wild kiang.